The Contribution of Intellectual Intelligence, Emotional Intelligence, and Spiritual Intelligence on Employee Performance - Fitriani Latief; Asniwati Asniwati (Jurnal Manajemen Bisnis, 2023)
This study aims to test and analyze intellectual intelligence, emotional intelligence, and spritual intelligence on employee performance at the South Sulawesi Province Food Security Service. The population in this study was employees of the South Sulawesi Province Food Security Service, which amounted to 47 employees. Sampling in this study used census sampling technique, where all members of the population were used as samples. The source of this research data is primary data, which is data obtained from the results of distributing questionnaires to all respondents. The statistical method used to test the hypothesis uses the help of the SPSS application. In addition, in maintaining data quality, research uses validity tests and reliability tests. The results showed that intellectual intelligence, emotional intelligence, and spritual intelligence had a positive and significant effect on the Performance of Employee Employees at the South Sulawesi Province Food Security Service